Thermo-economic Impact from Using Exhaust Gases Heat Lost for Power Generation - Khrebish, Hussam T.; Sultan, Hussien S. (Basrah Journal for Engineering Sciences, 2019)
The heat lost from gas turbine power plants with exhaust gases represents the most important source for lowering its thermal efficiency. Also, the gas turbine thermal efficiency affected significantly with the ambient surrounding temperature. Al-Najybia gas-turbine power plant in Basrah, Iraq is choosing as a case study. The power plant consists of four units with a capacity of 125 MW for each unit. In the present study, all the calculations are performed for one unit only. Firstly the thermal impact is studied in terms of energy analysis for Al-Najybia gas turbine power plant (GTPP) for different ambient temperature for twelve months. Also, the economic loss a companied the heat lost with exhaust gases for different ambient temperature are estimated. Secondly, the thermo-economic improvement from coupling the GTPP with a heat recovery system is studied. For gas-steam combined cycle, the performance and economic analysis are performed. The results show that, the output power and thermal efficiency are decreased by 0.97 MW and 0.0726% respectively for each unit temperature rise of the ambient temperature. For the combined gas-steam power plant the percentage increasing of the thermal efficiency is approximately 46.4%. The results indicate the combined cycle power plant (CCPP) is very important to increase electrical capacity. From the economic analysis, the economic gain due to using HRB is 75757 $ per month.